2008
DOI: 10.4049/jimmunol.181.1.346
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Regulates Expression of VEGFR1 in Myeloid Cells: Link to Tumor-Induced Immune Suppression in Renal Cell Carcinoma

Abstract: Metastatic renal cell carcinoma (RCC) associates with overproduction of vascular endothelial growth factor (VEGF) due to the mutation/inactivation of the von Hippel-Lindau (VHL) tumor suppressor gene. Herein we demonstrate that implantation of human RCC tumor cells into athymic nude mice promotes the appearance of VEGF receptor 1 (VEGFR1)/CD11b double-positive myeloid cells in peripheral blood. Avastin-mediated VEGF neutralization was capable of significantly reducing the numbers of circulating VEGFR1+ myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
167
1
4

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(178 citation statements)
references
References 38 publications
6
167
1
4
Order By: Relevance
“…This observation is generally consistent with previous findings that granulocytic MDSCs are elevated in RCC patients in the mononuclear fraction of density gradient centrifugation-purified cells (21)(22)(23)(24). However, these results are not directly comparable because we performed our flow assays on unfractionated whole blood.…”
Section: Discussionsupporting
confidence: 76%
“…This observation is generally consistent with previous findings that granulocytic MDSCs are elevated in RCC patients in the mononuclear fraction of density gradient centrifugation-purified cells (21)(22)(23)(24). However, these results are not directly comparable because we performed our flow assays on unfractionated whole blood.…”
Section: Discussionsupporting
confidence: 76%
“…Continuous VEGF infusion in naive mice induced MDSC formation via VEGFR2 signaling (28) in one report, whereas MDSC accumulation in mice bearing colon tumors has been attributed to stem cell factor (46). Indeed, experiments ongoing in our laboratory as well as those published have identified a portion of MDSC, which express VEGFR1 and VEGFR2 (47). 9 Sunitinib-targeted receptors include all of those implicated thus far (VEGFR and c-kit), among others such as platelet-derived growth factor, Flt3, and CSF-1 receptor whose mechanistic importance cannot be ruled out (11).…”
Section: Discussionmentioning
confidence: 96%
“…+ cells in peripheral blood after treatment with bevacizumab in the case with renal cell carcinoma [80]. They showed that CD11b + VEGFR1…”
Section: Anti-vegf Treatment Could Promote Antitumor Immune Responsesmentioning
confidence: 99%